2020
DOI: 10.2196/18725
|View full text |Cite
|
Sign up to set email alerts
|

Patient Challenges and Needs in Comprehending Laboratory Test Results: Mixed Methods Study

Abstract: Notes: Questions with a hash tag (#) are displayed only when certain response is provided. Questions with an asterisk (*) allow participants to select more than one options. Screen Questions Did you take any clinical lab test (e.g., blood test, urine test, MRI, CT-scan) over the past six months? • Yes • No

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 49 publications
(60 reference statements)
1
45
0
Order By: Relevance
“…Thus they may make decisions about their health that are based on incorrect information, with negative consequences for their health [ 25 ]. Health check participants have requested trustworthy educational resources online [ 26 ]. In Sweden and several other countries, the national health care system provides an online portal with quality-ensured health information to the public (e.g., Medlineplus.gov, NHS.uk) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus they may make decisions about their health that are based on incorrect information, with negative consequences for their health [ 25 ]. Health check participants have requested trustworthy educational resources online [ 26 ]. In Sweden and several other countries, the national health care system provides an online portal with quality-ensured health information to the public (e.g., Medlineplus.gov, NHS.uk) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, although this study was specific to one citizen, the journey map concept could be modified and used to synthesize common issues experienced by multiple citizens. This study revealed that providing citizens with access to their test results via portals offers some value, but these systems may not meet their diverse needs [8]. Therefore, with the advent of digital health technologies and services, considerations to eHealth literacy, the digital divide and health equity are paramount.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, in conjunction with the features and readily available data that digital health tools offer, it is imperative to understand the context in which they will be accessed, used, and interpreted along the patient journey [7]. Merely, providing citizens with access to their health information does not guarantee comprehension [8] or equitable distribution of health services. Further, the broad expansion of technologies can exacerbate health care disparities (i.e., reduce health equity) by offering more services to those who are already better positioned, while leaving behind people without adequate infrastructure (i.e., no access) or that do not have the knowledge or desire to use technology [9].…”
Section: Introductionmentioning
confidence: 99%
“…1,16,19 After viewing results, patients might seek information by calling or messaging clinicians (thereby increasing clinician workload), searching the internet, or consulting family and friends, with varied success toward understanding results accurately. 8,17 Research should explore how clinicians can best set patients' expectations at the time of referral or testing for potential ambiguity in portal-delivered results (Table 1, skill 2) and address patient understanding of results in follow-up discussions (Table 1, skill 4).…”
Section: Opportunities and Challenges In Communication Because Of Dir...mentioning
confidence: 99%